Code-switching in Philippine print ads a syntactico-pragmatic description - Dayag, Danilo T. (2002)
This study was an attempt to describe the syntactic and pragmatic properties of code-switching in Philippine print ads. It aimed to (1) analyzed for which product types code-switching is most extensively used in ads published in Philippine broad sheets; (2) identify in which section of the newspaper code-switched ads appear most often; (3) describe the syntactic patterns of code-switches in Philippine print ads; and (4) analyze code-switching in the three newspapers in terms of discourse function. The corpus of the study consisted of 41 ads for four specific types of consumer nondurables taken from Philippine Daily Inquirer, Manila Bulletin, and Philippine Star. These were gathered in June, July, and August 2000. Text analysis was the dominant analytical tool. For syntactic properties of code-switching, analysis was based on Poplach (1980). For discourse micro-functions, Dayag (1999), which was patterned after Searle (1979), was helpful. Findings of the study include the following: (1) Ads for the product category food, drinks, and condiments are where code-switching is most extensively used; (2) Code-switched ads most often appear in the lifestyle section of the Philippine newspaper; (3) Intrasentential code-switches are most extensively used in the ads, and the typical combination in Tagalog-with-English-elements; (4) In terms of discourse function, assertion is the principal function played by code-switching in Philippine print ads, followed by description/illustration and identification/naming referring. Recommendations for future studies include characterizing print ads as discourse type in term of M.A.K. Halliday's metafunctions and contextual dimensions, linguistic properties of Philippine English in print ads, and pragmatic analysis of TV commercials in the Philippines.
Includes bibliographical references (page 50).